Economic empowerment of rural and urban women in India: A comparative analysis - Biswas, Bapan; Banu, Nasrin (Spatial information research (Online), 2023)
The status of women is intimately connected with their economic situation depending upon the opportunity for participation in economic activities. The census data, 2011 shows a vast inequality between rural and urban women work participation as urban women associated with economic activities is just about half of the rural women. Available pieces of the literature revealed how the employment status of women makes them empower, but limited research has been conducted on the comparison of women empowerment in the rural-urban area in different dimensions. In this perspective, assuming that women’s economic empowerment is dependent on work participation, the present study attempts to compare the magnitude of women’s economic empowerment in urban India with its rural counterpart, focusing on various dimensions of work participation. This study is entirely based on secondary databases collected from the Census of India, 2011 and Periodic Labour Force Survey (PLFS) 2019-20. Economic Empowerment Index (EEI) of women has been measured with the help of women work participation, literate women work share, educational level-wise women work participation, work share by married women and job profile wise women work share using the widely adopted normalization technique. The result of the study is showing that the rural women are more engaged in the workforce in all the selected dimensions. The overall analysis is reflected in EEI, which proves that rural women are more economically empowered in comparison with their urban counterparts.